Interpretation of the Engravings in Early 16th-century Parisian Liturgy Books: From Alfred W. Pollard to Contemporary Conceptions of Visual Narrative - Subbotina, Olga V. (Actual Problems of Theory and History of Art, 2021)
All major Parisian publishers and printers of the first half of the 16th century either ordered or printed a vast range of liturgy books. It was in the 19th century when scientific interest in the study of such literature arose and the first catalogs and researches appeared. During this period, classification and general description of these books was made, and the main list of publishers had been formed. In the 1890s, the English researcher A. W. Pollard published “Early Illustrated Books”. This study caused the interest in the French liturgy book as an object of art noteworthy both at the level of the main illustrative set and the peripheral small images and ornamentation. This approach was further developed by authors of the next generation in the first decades of the 21st century, when in the articles and dissertations the following issues are considered: images in the margins, the structure and specific features of the visual narrative of liturgy books. The paper is about small woodcuts in the margins of liturgy books of the first half of the 16th century from the collections of the Russian Academy of Sciences Library and the Russian National Library. We will distinguish between images and “para-images” according to the structuralist division of the main texts and “paratexts”, which include engravings in the margins of the Book of Hours and Missals. Based on recent studies of visual narrative (W. Kemp, G. Horvàth), the author will analyse two important problems for the theme: reuse the same engravings and visual narrative’s coherence.